Novel 3D copper nanoparticles/chitosan/nanoporous alumina (CCSA) membranes with catalytic activity. Characterization and performance in the reduction of methylene blue. (10th February 2019) - Durán, B.; Hevia, S.A.; Molero, L.; Isaacs, M.; Bonardd, S.; Diaz Diaz, D.; Leiva, A.; Saldías, C.
Abstract: Herein, we report the surface modification of H2 O2 -treated nanoporous alumina (anodic aluminum oxide, AAO) membranes with chitosan (CS) by a solution casting method. Later, copper nanoparticles were incorporated into this CS-AAO membrane by immersion in an aqueous solution of a copper salt precursor and subsequent reduction using NaBH4 . The IR spectra and energy dispersive X-ray spectroscopy (EDS) analyses helped to confirm the presence of CS and copper nanoparticles both on the surface and inside the nanochannels of this AAO membrane (denoted CCSA). Notable differences in the surface energy, surface topography and morphology were observed between the CS-AAO and CCSA membranes. The catalytic performance of the CCSA membrane was tested in the reduction of methylene blue (MB).Our findings revealed that this system adequately combines the attractive properties of supporting of the AAO membranes, ion retention by CS and the catalytic activity of copper nanoparticles into a tridimensional array. Finally, the recyclability of the CCSA membrane was also assessed. The results showed that the performance of this membrane was not dramatically affected after four cycles of use.